Assessment of fluidity retention, mechanical strength and cost production of blended cement self-compacting concrete using the concept of a performance index - Boukhelkhal Aboubakeur; Kenai Said (Fracture and Structural Integrity)
Construction industry consumes a large amount of natural resources and energy and produces high amount of CO2 emissions and waste materials. For more sustainable construction industry, various waste materials are used as natural aggregates substitution or as cement replacement materials. In this paper, marble powder (MP) is used as a substitution to ordinary Portland cement (OPC) and its effects on some fresh and hardened properties of self-compacting concrete (SCC) are investigated. The tests at the fresh state were slump flow, L-box and sieve segregation. To assess the fluidity retention, slump flow loss was measured after 30, 60 and 90 minutes. At hardened state, two tests were realized: compressive strength and static segregation. The results indicate that adding MP improved the fresh properties but decreased the compressive strength of SCC. Adding MP allows to maintain the fluidity of SCC until 90 minutes. Production cost can be reduced by using MP. The performance approach showed that a substitution level of MP of 20% is adequate to produce an eco-efficient SCC with high fluidity and acceptable strength.